Interventional cardiology in Poland in 2020 – impact of the COVID-19 pandemic. Annual summary report of the Association of Cardiovascular Interventions of the Polish Cardiac Society and Jagiellonian University Medical College* - Siudak, Zbigniew; Dudek, Dariusz; Grygier, Marek; Araszkiewicz, Aleksander; Dąbrowski, Maciej; Kusa, Jacek; Hawranek, Michał; Huczek, Zenon; Kralisz, Paweł; Roleder, Tomasz; Wojakowski, Wojciech; Parma, Radosław; et al. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
As we have previously reported, the ORPKI electronic data capture is monitored continuously and modified according to the needs of the rapidly changing everyday practice of interventional cardiology not only in Poland but also worldwide as required by ESC guidelines [1, 2]. The database is endorsed by the Association of Cardiovascular Interventions of the Polish Cardiac Society (AISN PTK) and is daily operated by the Jagiellonian University Medical College, with currently 154 interventional cardiology centers in Poland reporting. ORPKI database analysis of various trends and patterns is published each year [3–5]. On 31st of December 2020 there were 575 PCI operators certified by the AISN PTK in Poland.